2014
DOI: 10.1021/jo501151w
|View full text |Cite
|
Sign up to set email alerts
|

Double-Coding Nucleic Acids: Introduction of a Nucleobase Sequence in the Major Groove of the DNA Duplex Using Double-Headed Nucleotides

Abstract: A series of double-headed nucleosides were synthesized using the Sonogashira cross-coupling reaction. In the reactions, additional nucleobases (thymine, cytosine, adenine, or guanine) were attached to the 5-position of 2'-deoxyuridine or 2'-deoxycytidine through a propyne linker. The modified nucleosides were incorporated into oligonucleotides, and these were combined in different duplexes that were analyzed by thermal denaturation studies. All of the monomers were well tolerated in the DNA duplexes and induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…4,5 In this context, an interesting modification is the addition of a second nucleobase to the nucleotide skeletonthe so-called double-headed nucleotide. 6 We have previously reported the synthesis and recognition properties of several double-headed nucleotides with the additional nucleobase attached to the 5´-, 2´or 5-position through various linkers, [7][8][9][10][11][12][13][14][15][16][17] while others have used the 4´-position or the 2´-N of amino-LNA as attachment points. 18,19 For the dU B design (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In this context, an interesting modification is the addition of a second nucleobase to the nucleotide skeletonthe so-called double-headed nucleotide. 6 We have previously reported the synthesis and recognition properties of several double-headed nucleotides with the additional nucleobase attached to the 5´-, 2´or 5-position through various linkers, [7][8][9][10][11][12][13][14][15][16][17] while others have used the 4´-position or the 2´-N of amino-LNA as attachment points. 18,19 For the dU B design (Fig.…”
mentioning
confidence: 99%
“…To get further insight into the effect of double-headed nucleotides on both duplex and triplex stability, a series of six modified oligonucleotides were synthesized. All of these were based on the same 16-mer homo-pyrimidine TFO sequence, which has been studied before, 15,17,20 having single, double or triple incorporations of either C C , U T or both in exchange for the corresponding dinucleotides (Fig. 3).…”
mentioning
confidence: 99%
“…In recent years, several double-headed nucleoside designs have been presented in the literature. [7][8][9][10][11][12][13] Our previous work has shown that depending on the site of attachment, the additional nucleobase can be positioned in the minor groove, [14][15][16][17] the major groove, [18][19][20] or the center of a DNA duplex. [21][22][23] In the latter case, given that the additional nucleobase is linked through a methylene to the 2'-position of 2'-deoxyuridine or arabinouridine (Figure 1, U X ), the doubleheaded nucleotide has been shown to behave as a condensed dinucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…T T, C T, A T, G T, T C, C C, A C and G C). 21 These were introduced into oligonucleotides including fully modified sequences that when mixed with complementary DNA, forms very stable duplexes with a full array of additional nucleobases in the major groove. The thermal stability of these duplexes was increased as compared to unmodified duplexes, mainly due to the stacking from the increased π-system formed by the propyne linkers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the array of nucleobases in the major groove can take several conformations due to the flexibility in the same propyne linkers. 21 Herein, we introduce four new double-headed nucleotide analogues where the propyne linker of T T is replaced with more rigid linkers separating the two thymine nucleobases. A phenyl group is introduced in the linker with m-or p-substitution either with or without an acetylene spacer giving the monomers X, Y, Z and W, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%